PROGNOSTIC VALUE OF TUMOR MARKERS KI67 AND P53 IN DETECTING RECURRENCE OF BLADDER CANCER - Tillyashaykhov M.N; Boyko E.V; Yusupov Sh.Kh; Sullettbaev N.B; Dyu A.V (Western European Studies, 2024)
Bladder cancer (BC) remains one of the predominant pathologies in onco-urological practice and poses a significant challenge for global healthcare. Understanding the risk factors and prognosis of this disease can improve prevention, early detection, and treatment of this type of cancer.
Keywords: bladder cancer; urothelial carcinoma; immunohistochemistry